«…INSPIRING AND ARTISTIC ASPECT OF THE WORLD AS OBSERVED BY AN ARTIST’S EYE»: THE MEMOIRS BY OLEKSA HRYSHCHENKO - Мочернюк, Н. Д. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The memoirs of the Ukrainian artist Oleksa Hryshchenko have been examined in the paper («My years in Constantinople» (1930), «Ukraine of my blue day» (1958), «My encounters and conversations with French artists» (1962), «Year of storm and stress» (1967)). The first two works have been examined carefully. The attention is paid to the thematic, compositional, narrative and chronotopic aspects of the author’s books.